Kavita 93 : a selection from contemporary Indian poetry - Soccidānandan, 1946-; Dāsa, Jagannātha Prasāda, 1936-; Poetry Society (India) (New Delhi : Virgo Publications, 1994)
Selected Indic poetry translated into English.
Copyright: The Poetry Society (India) and the poets.
Mode of access: Internet.
Keywords: Indic poetry -- 20th century -- Translations into English